Bacterial biofilms in patients with chronic rhinosinusitis - Dworniczek, E; Fraczek, M; Seniuk, A; Kassner, J; Sobieszczańska, B; Adamski, J; Ciesielska, U (Folia microbiologica, 2009)
The possible presence of biofilms was examined in mucosal specimens of 15 patients, undergoing functional endoscopic sinus surgery or a modified Caldwell-Luc approach for chronic rhinosinusitis (CRS). Biofilms were found in 7 of the 15 patients, positive cultures being obtained in most samples, which supports the role of biofilms as an important factor in the pathogenesis of CRS.
Keywords: mikroskopie elektronová rastrovací; Endoscopy; Adolescent; Rhinitis; Adult; Male; lidé; lidé středního věku; Humans; Middle Aged; rýma; Sinusitis; Young Adult; sinusitida; Biofilms; Microscopy, Electron, Scanning; mužské pohlaví; dospělí; chronická nemoc; mladý dospělý; Chronic Disease; ženské pohlaví; mladiství; Female; endoskopie; Nasal Mucosa; nosní sliznice; biofilmy